2002
DOI: 10.1007/pl00007863
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of acute symptomatic occlusions of the internal carotid artery

Abstract: The present study showed that recanalization of the occluded ICA in acute stroke patients is more frequent than generally presumed. CCDS should be routinely performed in the follow-up of stroke patients as spontaneous recanalization may influence clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 19 publications
2
56
1
Order By: Relevance
“…2,3 In this group of patients, early restoration of flow in the occluded ICA may improve the symptoms of acute stroke, prevent stroke deterioration, and reduce the long-term stroke recurrence risk. Some authors have reported successful revascularization of patients with acute stroke symptoms secondary to ICA occlusions.…”
mentioning
confidence: 99%
“…2,3 In this group of patients, early restoration of flow in the occluded ICA may improve the symptoms of acute stroke, prevent stroke deterioration, and reduce the long-term stroke recurrence risk. Some authors have reported successful revascularization of patients with acute stroke symptoms secondary to ICA occlusions.…”
mentioning
confidence: 99%
“…2,[16][17][18] The rate of recanalization is dependent on several factors, such as the type of acute treatment and the segment affected. 17,19 This is the first study with a prospective design on the occurrence of a residual high-grade stenosis after recanalization of an extracranial ICA occlusion in the acute stage of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…18 Two smaller studies reported a residual high-grade stenosis in 1 of 12 (8.3%) patients and 2 of 20 (10.0%) patients, respectively. 2,16 More than half of the patients with a residual high-grade stenosis in our study population underwent CEA or carotid stenting. In addition, CEA could also be considered in patients with a residual stenosis of 50% to 69%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aside, we have found only a few cases of ICA SR at its origin or in its siphon, demonstrated by USG or AG, in the literature [5][6][7][8][9][10][11][12] . So far to date, no reliable data have been published on the incidence and clinical consequences of SR of the extracranial ICA occlusion 6 .…”
mentioning
confidence: 99%